2015
DOI: 10.1089/thy.2015.0278
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mutations Detected Preoperatively May Predict Aggressive Behavior of Papillary Thyroid Cancer and Guide Management—A Case Report

Abstract: The judicious indication of FNA and use of molecular screening can potentially help in predicting aggressive behavior of small-sized thyroid cancers and in identifying patients who may benefit from early and more extensive therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
2
16
0
2
Order By: Relevance
“…These clinicopathological data strongly support a prominent role of TERT promoter mutations in the tumorigenesis and progression of thyroid cancer, which is well corroborated by previous results on similar differential expression patterns of TERT in benign and malignant thyroid tumors. As such, TERT promoter mutations are promising diagnostic and prognostic genetic markers for thyroid cancer, which is highly applicable clinically as demonstrated recently by applying them to thyroid fine needle aspiration biopsy for such purposes (Liu & Xing 2014; Nikiforov et al 2014; Shrestha et al 2015). Future studies will need to more specifically define such clinical utilities, elucidate the biological mechanisms of the role of TERT promoter mutations in thyroid tumorigenesis, and explore and establish the therapeutic utilities of targeting TERT for thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These clinicopathological data strongly support a prominent role of TERT promoter mutations in the tumorigenesis and progression of thyroid cancer, which is well corroborated by previous results on similar differential expression patterns of TERT in benign and malignant thyroid tumors. As such, TERT promoter mutations are promising diagnostic and prognostic genetic markers for thyroid cancer, which is highly applicable clinically as demonstrated recently by applying them to thyroid fine needle aspiration biopsy for such purposes (Liu & Xing 2014; Nikiforov et al 2014; Shrestha et al 2015). Future studies will need to more specifically define such clinical utilities, elucidate the biological mechanisms of the role of TERT promoter mutations in thyroid tumorigenesis, and explore and establish the therapeutic utilities of targeting TERT for thyroid cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Most WDTC have indolent behavior, and the early identification of high-risk patients who may exhibit a more aggressive course of the disease is important in order to try to find a way of preventing unfavorable developments [Shrestha et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the feasibility of mutational analysis in fine needle biopsy aspirates [Xing et al, 2014;Shrestha et al, 2015;Crescenzi et al, 2016] allowing preoperatively to evaluate the mutational tumor profile. The benefits of this approach are evident, for example, in undetermined cytology specimens in which the identification of a BRAF V600E mutation is almost 100% diagnostic of PTC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations